Designing inter-religious dialogue model for the grassroots: a preliminary survey - Ab. Majid, Arfah; Ibrahim, Haslina; Adnan, Zatul Himmah; Lee, Yok Fee; Ab. Halim, Adlina (Asian Scholars Network, 2020)
In order to strengthen national unity and integration, the dialogue culture needs to be cultivated in Malaysia (Azizan Baharudin, 2008). Moreover, Malaysian society is still grounded with prejudice as this problem was never wisely dealt with (Abdul Rahman Embong, 2001). Nevertheless, the nature of current practice of inter-religious dialogue is too philosophical and theological thus the participation is limited to the elite or intellectuals. If the present model of inter-religious dialogue is meant only for the elite and not for the grassroots, how could it be the best platform for national unity and integration?. Based on this argument, an inter-religious dialogue model that is more appropriate for the grassroots need to be developed. Therefore, present research aims at exploring the nature of Malaysian society and the reality of inter-religious relations in Malaysia as an early effort to develop the inter-religious dialogue model. To achieve this goal, a survey was conducted on 426 multi-religious respondents around Klang Valley. Among the variables measured to assess the nature of Malaysian society and the reality of inter-religious relations in Malaysia were, motivation and skills in inter-religious engagement, prejudice, quantity of contact, quality of contact and inter-religious understanding. Descriptive statistical analysis was employed to determine the level of variables while inferential statistical analysis was used to assess the correlation between prejudice and selected variables (i.e. skills in inter-religious engagement and quality of contact) and correlation between skills in inter-religious engagement and quality of contact. The findings suggest that Malaysian society in general has a high level of motivation and skills in inter-religious engagement, quality of contact and inter-religious understanding. The level of prejudice and the level of quantity of contact on the other hand are recorded as low. The low level of quantity of contact however can not to be underestimated since the correlation analysis has demonstrated that contact is negatively correlated with prejudice. This correlation means low level of contact is associated with high level of prejudice while high level of contact is associated with low level of prejudice. Lack of contact among Malaysian is feared can increase prejudice. All these findings envisage the need and feasibility to implement inter-religious dialogue in Malaysia. The data in this preliminary survey will guide the researcher in determining the stages, contents, processes and specific activities related to the design of inter-religious dialogue for the grassroots. Keywords: Inter-religious dialogue, design, grassroots, prejudice